2009
DOI: 10.2308/jis.2009.23.2.49
|View full text |Cite
|
Sign up to set email alerts
|

Assurance on XBRL-Related Documents: The Case of United Technologies Corporation

Abstract: The eXtensible Business Reporting Language (XBRL) was developed to provide financial information users with a standardized method to prepare, publish, and exchange business information in digital format. XBRL is being used around the world for financial reporting and government e-filings. Although there has been growing awareness about assurance issues related to the use of XBRL, current audit practices and standards fall short of providing the needed guidance for the provision of assurance on XBRL-Related Doc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(37 citation statements)
references
References 0 publications
0
37
0
Order By: Relevance
“…They found a variety of errors in filings, including differences between the XBRL instance document and the official filing and inconsistent use of company identifiers. In a recent case study, Boritz and No (2009) conduct mock assurance of a filing of United Technologies Corporation under that program. They found that while there were errors (e.g., redundant extensions), the instance document was a ''complete and accurate reflection" of the company's original financial statements.…”
Section: Introductionmentioning
confidence: 98%
“…They found a variety of errors in filings, including differences between the XBRL instance document and the official filing and inconsistent use of company identifiers. In a recent case study, Boritz and No (2009) conduct mock assurance of a filing of United Technologies Corporation under that program. They found that while there were errors (e.g., redundant extensions), the instance document was a ''complete and accurate reflection" of the company's original financial statements.…”
Section: Introductionmentioning
confidence: 98%
“…They argue that XBRL may improve the quality of financial information by virtue of well-defined standard taxonomies and a radical increase in the degree of automation facilitated by those taxonomies. Other studies (Boritz and No 2003;Cohen et al 2003;Lymer and Debreceny 2003;Boritz and No 2008;Plumlee and Plumlee 2008;Boritz and No 2009;Srivastava and Kogan 2009) consider the role of taxonomies for assurance on XBRL financial reporting, addressing the problem of data quality. In particular, Srivastava and Kogan (2009) develop a conceptual framework of assertions for providing assurance on XBRL instance documents.…”
Section: Literature Review Of Xbrl Taxonomiesmentioning
confidence: 99%
“…Based on our review of the aforementioned guidelines (AICPA, 2003;2009;AWG, 2006;PCAOB, 2005) and other literature discussing XBRL assurance issues (AICPA, 2008;Boritz and No, 2009;Plumlee and Plumlee, 2008;Srivastava and Kogan, 2010;XBRL.US, 2008), we developed the following assurance framework for XBRL-related documents.…”
Section: An Assurance Framework For Xbrl-related Documents and Audit mentioning
confidence: 99%
“…The limited guidance for and experience with the creation of XBRL documents raise questions about the quality of XBRL-tagged information, which, in turn, leads to assurance issues related to the use of XBRL (Boritz and No, 2009;2004a;2008;Elliott, 2002;Farewell and Pinsker, 2005;McGuire et al, 2006;Pinsker, 2003;Plumlee and Plumlee, 2008). The goals of this paper are to identify a set of specific audit objectives and related audit tasks for XBRL-tagged information and to discuss how computer-assisted audit functions can be used to carry out those audit tasks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation